Pengaruh Penggunaan Aplikasi Power BI dalam Analisis Produksi di Pabrik Karton Box XYZ di Provinsi Lampung, untuk Meningkatkan Efisiensi dan Pengambilan Keputusan - Angga Darma Prabowo; Dondi Kurniawan; Sabiqunassabiqun; Rizal Nazarrudin; Nurcahya Nugraha; Eko Wahyu Saputra; Mochammad Resha; Saputra, Rizal Adi (Nemui Nyimah, 2025)
This study aims to analyze the impact of using Power BI in improving efficiency and decision-making at Karton Box XYZ Factory in Lampung Province. Using action research methodology, production data, machine efficiency, product quality, raw material usage, and response time data were collected and analyzed before and after the implementation of Power BI. The results show that the implementation of Power BI successfully increased daily production, machine efficiency, product quality, as well as reduced raw material waste and response time. With its ability to visualize data in real-time, Power BI assisted the factory in optimizing production processes and enhancing operational efficiency. This study concludes that the use of Power BI has a positive impact on the factory's operational performance, boosting competitiveness, and supporting faster and more accurate data-driven decision-making.